Epidemiological features of road traffic accidents among young adults in a semi urban community of Southern Nigeria - M I Ntaji (Nigerian Postgraduate Medical Journal, 2015)
Aims and objectives: This study determined the history of reported road traffic accidents among the young adult population, and the prevalence of injury, as well as report of subjects′ witness of involved accident deaths among the accident victims. Also, it described the sociodemographic factors associated with increased incidence of RTA. The time of the day, month and year of accident occurrence were also described. Materials and methods: This descriptive cross sectional study was conducted among young adults of a semi urban community in Delta State, Nigeria. The study participants were selected by means of cluster sampling method. Researcher administered semi structured questionnaires were used to collect data. Results: Fifty-seven (34.5 %) of the 165 respondents had been involved in road traffic accident (RTA). The incidence rate of road traffic accident was 34.5%. The age group 15-19 years had the highest rate of RTA (45.0%) more than any other group. Males (38.7%) were more involved in RTA than the females (31.1%). The rate of injury was higher among the females (60.7%) than the males (58.6%). The two months with the highest rate of RTA were June (17.3%) and October (9.6%), while the least was recorded in February (3.8%). The RTA rate increased from 5.3% in 1997-2000 to 61.4% in 2009-2012. Conclusion: There is need to improve road safety education among the young adult, especially the adolescent with more effort during the rainy season.